La reconstrucción biográfico-narrativa del saber pedagógico en profesores del distrito con más de 20 años de experiencia profesional - Nixon Alirio Medina Talero (Cambios y Permanencias, 2017)
The research, with a narrative focus, explored the pedagogical knowledge of five teachers of natural sciences in the district. The analysis shows that the pedagogical knowledge is an implicit knowledge, transmitted in an artisan way during the initial formation, including the Normal School. Its construction appeals to the reflection on difficult experiences and actors with a contrast to the protagonists of the narrations, where the professional teaching practice (constitutive axis of knowledge) overflows institutional formalisms. The proposed narrative analysis constitutes a valuable contribution to qualitative research, does not fragment the narrative and confer unity of analysis on the teacher's narrative.